An Improved Method to Reduce Development Time for New Models of Proton - Nik Mohamed, Nik Mohd Zuki (2006)
Automotive industry in the world mostly depends on the new product development to enable it to stay in business. Therefore, car manufacturers should emphasis on various strategies and concepts that can be accepted by the local as well as overseas customers. This is particularly important in the automotive industry where radically shortened product development cycle time remains a crucial differentiating factor between the best performing companies and the rest of the industry. Every company seems to believe that time compression is always to be pursued, along with high quality products and low cost. Hence, a study of strategic methods to reduce development time for new model in automotive industry is presented in this thesis. The approach taken are by studying the existing practice in car development and suggesting various ways for method improvement. Car making process involved concept initialization, drawings, prototypes, trials and mass production. Throughout the research, factors of 4M (Man, Method, Material and Machine) are focused as the most important criterion in order to achieve the manufacture’s implementation objectives. The research started by identifying current problems by using 4M techniques. Then, data collection for new car model project implementation program in terms of time scheduling, product development process and production strategy was thoroughly studied and analyzed. By using the same 4M tools, a proposal was recommended to improve the existing practice in automotive manufacturing environment. The results are summarized in a table through SWOT analysis and by implementing these suggestions, it is hoped that car manufacturers can reduce the new car development time significantly. The thesis also recommends some important points for future research especially in term of project implementation and strategy.